Alpha‐7 nicotinic acetylcholine receptor (nAChR) agonist inhibits the development of endometriosis by regulating inflammation. (21st October 2016) - Yamada‐Nomoto, Kaori; Yoshino, Osamu; Akiyama, Ikumi; Ushijima, Akemi; Ono, Yosuke; Shima, Tomoko; Nakashima, Akitoshi; Hayashi, Shusaku; Kadowaki, Makoto; Osuga, Yutaka; Saito, Shigeru
Abstract: Objective: We investigated α‐7 nAchR expression in human peritoneal macrophages and examined whether activation of nAchR might be a new therapy for endometriosis. Materials and methods: Human peritoneal fluid mononuclear cells (PFMC) were stimulated with lipopolysaccharide (LPS) in the presence of α‐7 nAChR agonists. In a murine endometriosis model, α‐7 nAChR modulators were administered. Results: Human PFMC expressed α‐7 nAChR at the mRNA and protein levels. Activation of α‐7 nAChR with its agonists led to significant ( P <.01) suppression of LPS‐induced interleukin (IL) ‐1β expression. In a murine endometriosis model, one week after inoculation of endometrium to the peritoneal cavity, α‐7 nAChR agonist significantly suppressed the expression of IL‐1β mRNA ( P <.01), which was negated when α‐7 nAChR antagonist was administered simultaneously. α‐7 nAChR agonist significantly suppressed the formation of endometriotic lesions, which was reversed with α‐7 nAChR antagonist. Conclusion: Activation of nAChR might be a new candidate for treatment of endometriosis.